Компліментарні висловлювання із загальною оцінкою та оцінкою моральних якостей адресата в маніпулятивному дискурсі - Шкіцька, І.Ю. (Культура народов Причерноморья, 2013)
У статті схарактеризовано компліментарні висловлювання-маніпулеми, у яких предметом
схвалення постають загальна оцінка адресата і його моральні якості. Визначено та описано основні й
периферійні засоби вербалізації цих видів позитивної оцінки. Виявлено лексеми, що не спеціалізуються на
маркуванні загальної позитивної оцінки й оцінки моральних якостей. Ураховано характер ситуації та
мету маніпулятивно маркованої інтеракції, а також стать та статус її учасників. Установлено
частотність функціонування в маніпулятивному дискурсі компліментів, висловлених
симетричному / несиметричному за цими характеристиками комунікативному партнерові.
Ключові слова: компліментарне висловлювання-маніпулема, маніпулятивна стратегія позитиву, засіб
вербалізації, експресив, лексема. В статье охарактеризированы комплиментарные высказывания-манипулемы, в которых
предметом одобрения являются обшая оценка адресата и его моральные качества. Выделены и описаны
основные и периферические средства вербализации этих видов позитивной оценки. Определены лексемы,
которые не специализируются на передаче общей позитивной оценки и оценки моральных качеств.
Учтены характер ситуации и цели манипулятивно окрашенной интеракции, а также пол и статус её
участников. Установлена частотность функционирования в манипулятивном дискурсе комплиментов,
высказанных симметричному / несимметричному по этим характеристикам коммуникативному
партнеру.
Ключевые слова: комплиментарное высказывание-манипулема, манипулятивная стратегия позитива,
средство вербализации, экспрессив, лексема. In the article the manipulative complimentary utterances of an addressee's general assessment and
one’s moral qualities are characterized.
Complimentary utterances are presented as the main genre of the positively-coloured manipulative strategy.
This strategy aims at changing the emotional and mental state of an interlocutor, his or her behaviour, settings,
aspirations etc. A speaker makes some influence on a recipient by telling him or her pleasant information
particulary in the form of positively-evaluative utterances. The study has been carried out on the basis of the
analysis of the author's card index. That volume is more than 5,000 fragments of the dialogues of the works of
the Ukrainian fiction of the XIX-XXI centuries.
The basic and peripheral means of the verbalization of general positive valuation of an addressee, and one’s
moral qualities are identified and described. The lexemes, that are not specialized in the expression of the above
mentioned positively-evaluative values, are detected.
The utterances, which denote morality and spiritual strength, kindness, devotion, honesty and justice, altruism,
generosity, ability of having deep feelings to others, dedication and loyalty, etc., were allocated in the
compliments, which represent an interlocutor’s moral qualities. The extralinguistic factors, which have some
impact on a communicative situation, were taken into account in the study. Sex and status of participants of
communication are also taken into consideration.
The frequency of functioning compliments, that were expressed by symmetric or asymmetric communicative
partners on these characteristics in manipulative discourse, is established.
Key words: manipulative complimentary utterance, positively-coloured manipulative strategy, means of
verbalization, expressive, lexeme.